Effectiveness of the chemical ludo game on shifting equilibrium material and the factors that influence on learning outcomes - Resha Rinelda; Iswendi Iswendi (Jurnal Pijar Mipa, 2023)
This research is a continuation of development research with a 4-D model developed by Rini Fauza and Iswendi with the title Development of Ludo Chemistry Games as Learning Media on Material Shifting Equilibrium and Factors Affecting It Class XI SMA/MA which is valid but has not been tested for practicality and its effectiveness. This study aims to determine the level of practicality and effectiveness of chemical ludo games. The research design was the Pretest-Posttest Control Group Design. The research sample was XI MIPA 1 as the experimental class and XI MIPA 2 as the control class. Practicality data were analyzed with the practicality percentage and effectiveness data with the N-Gain test. The data analysis results on the practicality of teachers and students are in the very practical category. The results of the N-Gain analysis in the experimental class were 80% in the effective category and in the control class 74% in the quite effective category, which was supported by the learning outcomes of the experimental class, which were higher than the control class. The average posttest scores for the experimental and control classes were 84.83 and 81.17, respectively. The learning outcomes of the experimental class increased from the control class where tcount (2.465) > ttable (2.002) at a significant level α = 0.05. Ludo chemistry games as learning media are very practical and effective in improving student learning outcomes in the cognitive domain of class XI SMAN 1 Lubuk Basung.